An integration strategy for large enterprises - Risimic, D. (Yugoslav Journal of Operations Research; Vol 17 No 2 (2007): Vol. 17 No. 2, 2016)
Integration is the process of enabling a communication between disparate software components. Integration has been the burning issue for large enterprises in the last twenty years, due to the fact that 70% of the development and deployment budget is spent on integrating complex and heterogeneous back-end and front-end IT systems. The need to integrate existing applications is to support newer, faster, more accurate business processes and to provide meaningful, consistent management information. Historically, integration started with the introduction of point-to-point approaches evolving into simpler hub-andspoke topologies. These topologies were combined with custom remote procedure calls, distributed object technologies and message-oriented middleware (MOM), continued with enterprise application integration (EAI) and used an application server as a primary vehicle for integration. The current phase of the evolution is service-oriented architecture (SOA) combined with an enterprise service bus (ESB). Technical aspects of the comparison between the aforementioned technologies are analyzed and presented. The result of the study is the recommended integration strategy for large enterprises.